2006
DOI: 10.1073/pnas.0608502103
|View full text |Cite
|
Sign up to set email alerts
|

Unequal representation of cardinal vs. oblique orientations in the middle temporal visual area

Abstract: A possible neurobiological basis for the ''oblique effect'' is linked to the finding that more neural machinery is devoted to processing cardinal vs. oblique orientations in primary visual cortex (V1). We used optical imaging to determine whether more territory is devoted to processing horizontal and vertical orientations than oblique orientations in owl monkey middle temporal visual area (MT), a visual area highly sensitive to moving stimuli. We found that more of MT was devoted to representing cardinal than … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
49
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 54 publications
(55 citation statements)
references
References 40 publications
5
49
1
Order By: Relevance
“…The oblique effect was greater in the older groups, producing a larger difference between oblique and both horizontal and vertical trajectories in the older than in the younger groups. As we pointed out in the introduction, the oblique effect is usually attributed to a larger cardinal versus oblique neural representation in the primary visual cortex, and to the fact that horizontal and vertical orientations have a greater neuronal response (Li, Peterson, & Freeman, 2003;Xu, Collins, Khaytin, Kaas, & Casagrande, 2006). Older participants, whether or not they practiced a sport, exhibited a larger oblique effect than did the young adults, suggesting that the neural areas involved in the processing of oblique orientations decline with aging.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The oblique effect was greater in the older groups, producing a larger difference between oblique and both horizontal and vertical trajectories in the older than in the younger groups. As we pointed out in the introduction, the oblique effect is usually attributed to a larger cardinal versus oblique neural representation in the primary visual cortex, and to the fact that horizontal and vertical orientations have a greater neuronal response (Li, Peterson, & Freeman, 2003;Xu, Collins, Khaytin, Kaas, & Casagrande, 2006). Older participants, whether or not they practiced a sport, exhibited a larger oblique effect than did the young adults, suggesting that the neural areas involved in the processing of oblique orientations decline with aging.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, performance is better in horizontal than in diagonal trajectories (the so-called oblique effect; Appelle, 1972;Gros, Blake, & Hiris, 1998;Loffler & Orbach, 2001;Meng & Qian, 2005). This effect might be due to the larger cardinal (northsouth/east-west) versus oblique representation in the primary visual cortex, with the horizontal and vertical orientations producing greater neuronal responses (Li, Peterson, & Freeman, 2003;Xu, Collins, Khaytin, Kaas, & Casagrande, 2006).…”
Section: Physical Activity May Attenuate the Slowing Down Of Processimentioning
confidence: 99%
“…Previous observations (Furmanski and Engel 2000;Li et al 2003;Wang et al 2003;Xu et al 2006) have revealed that there is more 'neural machinery' devoted to processing the cardinal (horizontal and vertical) orientations than the oblique orientations; these results have been related to the greater psychophysical sensitivity to cardinal than oblique orientations ('the oblique eVect'; Appelle 1972).The higher activation to vertical than horizontal patterns might be taken to similarly reXect an imbalance in the number of neurons that prefer each orientation. However, a single unit study in cat V1 (Li et al 2003) found a greater abundance of neurons tuned to horizontal than to vertical orientations and studies in ferret V1 have shown that larger cortical areas are devoted to horizontal than to vertical orientations (Chapman and BonhoeVer 1998;Coppola et al 1998).…”
Section: Discussionmentioning
confidence: 98%
“…Stimuli oriented along the cardinal axes yield better psychophysical performance compared to obliquely oriented stimuli. In the visual cortices, both single-neuron responses and population responses reflect this psychophysical anisotropy by increased representational density along the cardinal axes (Furmanski and Engel 2000;Wang et al 2003;Xu et al 2006). Several studies suggest that the oblique effect originates in higher order cortices (Nasr and Tootell 2012;Liang et al 2007;Shen et al 2008), as the effect is stronger here compared to early sensory cortex (Shen et al 2008;Müller et al 2000), and the effect in early cortex is selectively abolished by temporal inactivation of higher order cortex (Shen et al 2008).…”
Section: Oblique Effect In Grids?mentioning
confidence: 97%
“…1). Further, using optical imaging in area MT (which shows movement and orientation selectivity for stimuli) in the visual system, Xu et al (2006) showed frequency plots of activation over the range of possible stimulus orientations. In these plots, there are quite distinct peaks with bimodal offsets from the cardinal axes (Fig.…”
Section: Oblique Effect In Grids?mentioning
confidence: 99%